IMPROVING ARTIFICIAL INTELLIGENCE MECHANISMS TO ENSURE MANAGEMENT EFFICIENCY IN SPECIALIZED EDUCATIONAL INSTITUTIONS - Ubbiyev, Alisher Tairovich (SCIENCE and SOCIETY, 2026)
This article proposes a management-oriented model for improving AI mechanisms in specialized educational institutions: data architecture, process analytics, forecasting and recommendation modules, a generative assistant, and risk management blocks are integrated into a unified “management control loop”.
Keywords: specialized educational institutions; management efficiency; artificial intelligence; educational analytics; algorithmic fairness